Hemodialysis versus peritoneal dialysis: an observational study in two international centers. Issue 1 (January 2018) - Lu, Renhua; Estremadoyro, Carla; Chen, Xiaohuan; Zhu, Mingli; Ribeiro, Leonardo C.; Yan, Yucheng; Brendolan, Alessandra; Fang, Wei; Crepaldi, Carlo; Ni, Zhaohui; Gu, Leyi; Ronco, Claudio
Introduction: Given that it is difficult to randomize end-stage renal disease (ESRD) patients to either hemodialysis (HD) or peritoneal dialysis (PD), differences between these renal replacement therapy (RRT) modalities are of major interest and remain controversial. Methods: All data on maintenance dialysis patients during 2009 to 2013 in the Renji Hospital in Shanghai, China and in the San Bortolo Hospital in Vicenza, Italy were selected. Patients who changed their therapy from HD to PD or PD to HD during this study were excluded. Results: 919 maintenance dialysis patients were included in the present study, including 509 patients on HD and 410 on PD. During the 5-year follow-up, mean arterial pressure (MAP) was higher in HD patients. The level of serum HCO3- was significantly better in PD patients than in HD patients. Phosphate was significantly higher in HD patients than in PD patients. With respect to lipid metabolism, triglyceride, total cholesterol and LDL were significantly higher in PD patients. Serum protein and albumin were higher in HD patients than in PD patients. Overall, 236 patients died (25.7%); 150 (16.3%) on HD and 86 (9.4%) on PD. The main cause of death in HD and PD patients was cerebral vascular disease and infection, respectively. After adjusting for dialysis vintage, the Kaplan-Meier patient survival was similar between HD and PD patients. Conclusions: Based on 5 years of data, we demonstrate that lipid metabolism and nutritional status were better in HD patients. However, blood pressure control, acid-base balance, phosphate (P) control were better in PD patients. The main cause of death in HD and PD was cerebral vascular disease and infection, respectively. Considering the dialysis vintage, the Kaplan-Meier patient survival was similar between HD and PD patients.